The “ Nasci Bem ” app for health professionals and families of newborns: construction, validation and evaluation - Ingrid Lucchese; Fernanda Garcia Bezerra Góes; Maithê de Carvalho e Lemos Goulart; Maria da Anunciação Silva; Aline Cerqueira Santos Santana da Silva; Liliane Faria da Silva (Revista Latino-Americana de Enfermagem)
Objective: to construct, validate and evaluate an app for mobile devices on humanized care practices for newborns at habitual risk in maternity wards, aimed at health professionals and family members. Method: a methodological study in seven stages: Literature review; Content organization; App construction; Validation by experts; Suitability after validation; Evaluation by the target audience; and Suitability after evaluation. A total of 22 experts took part in the validation and 21 individuals from the target audience in the evaluation. The instruments addressed content, face and/or motivation, with the System Usability Scale for usability. The following was calculated: Concordance Index and Usability Score. Results: in the validation process, the app achieved a Concordance Index of 0.97; ranging from 0.82 to 1.0 across the items analyzed. In the evaluation, the index was 0.99, varying from 0.95 to 1.0. In usability of the first version, the Concordance Index was 0.92 and the Usability Score was 93. In the second version, the index was 0.93 and the score was 94, indicating better usability achieved since the first version. Conclusion: the “ Nasci Bem ” app proved to be comprehensible, relevant, pertinent, efficient, easy to use, with low inconsistency, and with excellent potential to use it as educational technology for professionals and family members.